2023
DOI: 10.1007/s00018-022-04674-8
|View full text |Cite
|
Sign up to set email alerts
|

Rab26 controls secretory granule maturation and breakdown in Drosophila

Abstract: At the onset of Drosophila metamorphosis, plenty of secretory glue granules are released from salivary gland cells and the glue is deposited on the ventral side of the forming (pre)pupa to attach it to a dry surface. Prior to this, a poorly understood maturation process takes place during which secretory granules gradually grow via homotypic fusions, and their contents are reorganized. Here we show that the small GTPase Rab26 localizes to immature (smaller, non-acidic) glue granules and its presence prevents v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 50 publications
0
8
0
Order By: Relevance
“…Maturation of SGs is a multidimensional process that involves homotypic fusion, acidification, cargo condensation, and acquisition of membrane proteins that will steer SGs to the apical plasma membrane and contribute to the recognition, tethering and fusion (Boda et al, 2023; Ji et al, 2018; Nagy et al, 2022; Syed, Zhang, Tran, Bleck, & Ten Hagen, 2022). In the current work, we have shown that the exocyst participates in several aspects of SG maturation.…”
Section: Discussionmentioning
confidence: 99%
“…Maturation of SGs is a multidimensional process that involves homotypic fusion, acidification, cargo condensation, and acquisition of membrane proteins that will steer SGs to the apical plasma membrane and contribute to the recognition, tethering and fusion (Boda et al, 2023; Ji et al, 2018; Nagy et al, 2022; Syed, Zhang, Tran, Bleck, & Ten Hagen, 2022). In the current work, we have shown that the exocyst participates in several aspects of SG maturation.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to degradative crinosomes (at the prepupal stage -pp), ecdysone-induced progressive acidi cation also accompanies the maturation of SGs (2h before puparium formation -bpf), and is important for the remodeling of the inner structure of SGs and prepares them for exocytosis (priming) 3,[17][18][19]56,57 . Although both Vamp7 and Ykt6 proved to be required for the acidi cation of degradative crinosomes at the prepupal (pp) stage, it was still elusive whether these two R-SNAREs are also equally required for proper acidi cation of maturing SGs before their release.…”
Section: Acidi Cation Of Maturing Sgs Is Regulated Differently By Ykt...mentioning
confidence: 99%
“…The maturation and crinophagic decomposition of glue SGs both rely on a series of fusion events between SGs and lysosomes or endosomes 3,8,18,19,21,22 . Since Vamp7 and Ykt6 differentially affected SG maturation/acidi cation, we supposed that these R-SNAREs may mediate the fusion of SGs with different components of the endo-lysosomal compartment.…”
Section: Ykt6 and Vamp7 Differently Regulate The Fusion Of Arl8 + Lys...mentioning
confidence: 99%
See 2 more Smart Citations